DILEMA VIRUS CORONA TERHADAP PEREKONOMIAN INDONESIA - Rukmini, Meme (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the dilemma of Virus corona on the current Indonesian economy and this type of research is a type of research data analysis library, data reduction, data display and conclusions of this research results show the Virus corona-19 dilemma of the current Indonesian economy with various impacts occur in the economy due to the Virus corona-19 pandemic that is happening at the moment so it is necessary to know the dilemmas that occur namely termination of employment, difficulties in finding employment, community dilemmas to meet the needs of daily life and also a decline in income to meet the needs for everyday and dilemmas from all sectors of the economy in all fields also feel the dilemma of Virus corona-19.